Achieving highly selective electrocatalytic CO2 reduction by tuning CuO-Sb2O3 nanocomposites - Li, Y; Chu, S; Shen, H; Xia, Q; Robertson, AW; Masa, J; Siddiqui, U; Sun, Z (American Chemical Society, 2020)
The development of highly active and selective electrocatalysts with low cost and earth abundance for electrochemical CO2 reduction (ECR) remains an important area of interest. Here, we report the modification of CuO with other metal (Bi, Sb, Cd, and Zr) oxides to form bimetallic oxide nanocomposite catalysts exhibiting efficient ECR. In particular, CuO-Sb2O3 nanoparticles anchored on carbon black (CB) facilitated ECR selectively to CO at low overpotentials, providing a CO faradaic efficiency (FE) of up to 90.0% at −0.8 V versus reversible hydrogen electrode, in contrast to individual CuO/CB and Sb2O3/CB, which gave rise to CO FEs of less than 31.0%, outperforming many previously reported catalysts. A strong interaction between CuO and Sb2O3 is found, which likely contributes to the enhanced ECR activity.